Elise Ribaudo: capstone - Ribaudo, Elise, artist (Colorado State University. Libraries, 2021)
The artist's statement: Much of my work is focused around material exploration and experimentation. I'm always testing new unconventional materials and methods of creating. A common theme throughout my work is the distortion of the familiar into the unfamiliar, whether it be through materials or imagery. I want viewers to be intrigued yet disturbed when they look at my art; to simultaneously want for more and for less. This collaboration of the beautiful and the grotesque reflects my perception of myself and the world around me. I see myself as a complex and confusing mess of different layers, much like my work. I've always found art to be my most effective means of communication. Art allows me to express and explain myself when words fail me. Creative expression is a power that I am so grateful for; one that I want to share with as many people as I can. I want others to see the beauty in the grotesque the way that I do. There is always something beautiful to be uncovered, and there is always something ugly to be uncovered. My work is about finding them both and exhibiting them to the rest of the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing